Immediate reconstruction of a large myoepithelial carcinoma ex-pleomorphic adenoma in the palate with an osteocutaneous radial forearm flap: A case report - Tatsuya Sakaguchi; Shunichi Yoshida; Daisuke Kobayashi; Takeshi Karube; Shunsuke Ochiai; Seiji Asoda (DiscoverSys Inc., 2022)
Objective: A carcinoma ex-pleomorphic adenoma is caused by the long-term presence of pleomorphic adenoma. It is a relatively rare occurrence in the palatine glands.Methods: A 40-year-old man was referred to our department with a complaint of an intraoral mass. At the time of the initial examination, a large elastic hard mass of approximately 10 cm in diameter accompanied by ulceration in parts was found extending from the gingiva of the molar region in the right maxilla throughout the entire palate. Based on the imaging and histopathological examination findings, the clinical diagnosis was suspected to be malignant tumor of the palate.Results: The patient underwent palatal tumor enucleation, right-sided supraomohyoid neck dissection, and immediate reconstruction with an osteocutaneous radial forearm flap under general anesthesia. The histopathological diagnosis was myoepithelial carcinoma ex-pleomorphic adenoma. In addition, postoperative radiation therapy was performed. There has been no evidence of recurrence or metastasis for three years postoperatively.Conclusion: We report a case of large myoepithelial carcinoma ex-pleomorphic adenoma of the hard palate that was immediately reconstructed with an osteocutaneous radial forearm flap.